1996
DOI: 10.1002/(sici)1097-0010(199610)72:2<213::aid-jsfa641>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Guanidination of Lysine in Proteins

Abstract: The present study was conducted to compare the efficacy of five different reaction conditions on the guanidination of lysine in casein and to establish optimum lysine:O‐methylisourea (OMIU) for maximum guanidination of lysine in casein and soya bean meal. The results indicate that the presence of glycine–NaOH buffer is not required for guanidination of proteins at pH 10·5. A OMIU concentration of 0·4 M was found to be as effective as 0·6 M for guanidination. Both OMIU–hydrogen sulphate and free OMIU were equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
3
23
1
Order By: Relevance
“…To determine the TID and endogenous flow of lysine, the pigs were fed diets in which 50% of soyabean meal was replaced with guanidinated soyabean meal prepared in a 0.6 M O-methylisourea solution at pH 10.5 for 6 d (Imbeah et al, 1996). Prior to the homoarginine feeding, the pigs were fed three protein-free meals.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the TID and endogenous flow of lysine, the pigs were fed diets in which 50% of soyabean meal was replaced with guanidinated soyabean meal prepared in a 0.6 M O-methylisourea solution at pH 10.5 for 6 d (Imbeah et al, 1996). Prior to the homoarginine feeding, the pigs were fed three protein-free meals.…”
Section: Methodsmentioning
confidence: 99%
“…Maga (1981) also noted that the pH of the incubation mixture would drop during incubation at a rate of 0.1-0.2 pH units per 24 h and recommended pH adjustment on a daily basis. OMIU can be used as the buffer for maintaining the pH of the guanidination reaction mixture (Imbeah et al 1996). However, the low OMIU to lysine ratio used by Maga (1981) meant that as OMIU was consumed by the guanidination reaction, the amount of unreacted OMIU (the buffer) decreased and the pH dropped.…”
Section: Guanidination Methodsmentioning
confidence: 99%
“…For guanidinating the proteins in foods and feedstuffs, OMIU has been used as either the free base (Eklund et al 2013;Friesen et al 2006;Imbeah et al 1996;Mao et al 1993;Pahm et al 2010;Ravindran et al 2004;Rutherfurd and Moughan 1990;Torbatinejad et al 2005) or as the hydrogen sulphate salt (Fontaine et al 2007;Imbeah et al 1996). While the use of the free base is more prevalent, both forms of OMIU have been reported to be equally effective at guanidinating proteins (Imbeah et al 1996).…”
Section: Guanidination Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of Lys to homoarginine in the latter study, however, was calculated as the molar amount of homoarginine divided by the sum of the molar amounts of homoarginine and unreacted Lys. This manner of expressing conversions is often used (Maga, 1981;Rutherfurd and Moughan, 1990;Imbeah et al, 1996;Ravindran et al, 1996;Zhang et al, 2006;Pahm et al, 2008) but does not take into account the conversion of Lys to double derivatized Lys or other Lys derivatives. When applying this equation to the data of the current study, conversions of > 90% were found (data not shown).…”
Section: Optimization Of the Guanidination Reaction For Crystalline Lmentioning
confidence: 99%